Kerion of the Vulva Caused by Trichophyton mentagrophytes. Issue 3 (May 2014) - Bougrine, Amina; Villeneuve-Tang, Catherine; Bouffard, Danielle; Rouleau, Danielle; Chartier, Suzanne
Background: Deep dermatophytosis of genital skin is a rare clinical manifestation of infection by a common group of pathogens. Objective: We emphasize the importance of clinical suspicion and the use of accurate diagnostic methods in the evaluation of deep dermatophytosis. Methods: We report a single case of tinea pubis, kerion type, caused by Trichophyton mentagrophytes in an immunocompetent host. Results: A 54-year-old female presented with a suppurative infection of the vulva and pubis that was unresponsive to empirical antibiotic therapy. T. mentagrophytes was isolated. Oral itraconazole was initiated on the basis of clinical suspicion and continued for a total of 6 weeks. Conclusion: Accurate diagnosis and treatment of deep dermatophytosis of genital skin rests upon proper identification of the pathogen. Prompt initiation of treatment with an oral antifungal agent, such as itraconazole, should be undertaken in order to avoid irreversible scarring alopecia.